The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mnfr.201800283
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of the Nutrient Sensor mTORC1 in Myeloid Cells Induced by Tsc1 Deletion Protects Mice from Diet‐Induced Obesity

Abstract: Constitutive mTORC1 activation in myeloid cells protects mice from HFD-induced obesity, adipose tissue inflammation, and glucose intolerance by promoting macrophage polarization to M2 pro-resolution profile and increasing energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Mice were adapted to the metabolic cages for 2 consecutive days and evaluated for oxygen consumption (VO 2 ), carbon dioxide production (CO 2 ), spontaneous motor activity, and respiratory exchange ratio (RER, VCO 2 /VO 2 ratio) during 24 h in a Comprehensive Laboratory Monitoring System calorimeter (Columbus Instruments) as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Mice were adapted to the metabolic cages for 2 consecutive days and evaluated for oxygen consumption (VO 2 ), carbon dioxide production (CO 2 ), spontaneous motor activity, and respiratory exchange ratio (RER, VCO 2 /VO 2 ratio) during 24 h in a Comprehensive Laboratory Monitoring System calorimeter (Columbus Instruments) as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Constitutive mTORC1 activation in myeloid cells inhibits developing high-fat diet-induced obesity by promoting macrophage polarization to M2. Additionally, TSC1 deletion increases M2 macrophage polarization together with the mRNA levels of fatty acidbinding protein 4 and PPARγ, in an mTORC1-dependent manner (Paschoal et al 2018). Adipocyte-specific TSC1 deletion reduces visceral fat mass, as well as adipocyte number and diameter associated with increased lipolysis.…”
Section: Figurementioning
confidence: 95%
“…The mechanisms by which rapamycin induces those metabolic complications and promotes inflammation are still unknown. Several pieces of evidence indicate that mTORC1 is an important positive regulator of PPARγ transcriptional activity in adipocytes [ 42,44,49 ] and macrophages [ 50 ] raising the possibility that some of the aforementioned metabolic complications associated with rapamycin treatment are due to inhibition of this transcription factor. PPARγ is a nuclear receptor expressed in adipocytes and macrophages, among other cells, that regulates glucose and lipid metabolism and inflammatory status.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to adipocytes, myeloid cell Tsc1 deletion and therefore constitutive mTORC1 activation also protects mice from high‐fat diet‐induced obesity, white adipose tissue inflammation, and glucose intolerance by promoting an autonomous macrophage polarization to the alternative pro‐resolution M2 profile. [ 50 ] Mechanistically, enhanced M2 macrophage polarization induced by Tsc1 deletion is associated with increased PPARγ activity and oxidative metabolism. [ 50 ] Corroborating these findings, a recent study found that activation of the canonical Akt‐mTORC1 signaling pathway is a cardinal event in the macrophage polarization to M2 profile induced by IL‐4, through a mechanism involving ATP‐citrate lyase activation, histone acetylation and expression of a subset of M2‐related genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation